Protein interaction screening identifies SH3RF1 as a new regulator of FAT1 protein levels. Issue 4 (16th February 2017) - de Bock, Charles E.; Hughes, Michael R.; Snyder, Kimberly; Alley, Steven; Sadeqzadeh, Elham; Dun, Matt D.; McNagny, Kelly M.; Molloy, Timothy J.; Hondermarck, Hubert; Thorne, Rick F.
Abstract : Mutations and ectopic FAT1 cadherin expression are implicated in a broad spectrum of diseases ranging from developmental disorders to cancer. The regulation of FAT1 and its downstream signalling pathways remain incompletely understood. We hypothesized that identification of additional proteins interacting with the FAT1 cytoplasmic tail would further delineate its regulation and function. A yeast two‐hybrid library screen carried out against the juxtamembrane region of the cytoplasmic tail of FAT1 identified the E3 ubiquitin‐protein ligase SH3RF1 as the most frequently recovered protein‐binding partner. Ablating SH3RF1 using siRNA increased cellular FAT1 protein levels and stabilized expression at the cell surface, while overexpression of SH3RF1 reduced FAT1 levels. We conclude that SH3RF1 acts as a negative post‐translational regulator of FAT1 levels. Abstract :